Impact of Urban Land Use on Rainwater Quality: Case Study in Ilorin Metropolis, Nigeria - Agaja, Toluwalope Mubo; Towobola, David Olaoluwa (Journal of Environmental Geography, 2022)
This study assessed the physicochemical properties of rainwater in the urban land uses and observed the associated relationship between urban land uses and the physicochemical properties of rainwater. A total of 10 rainwater samples was collected and analysed for 15 physicochemical parameters namely: colour, conductivity, pH, total dissolved solids, turbidity, aluminium (Al3+), copper (Cu2+), iron (Fe2+), nitrate (NO3-), lead (Pb2+), nickel (Ni), sodium (Na+), phosphorus (K+), zinc (Zn2+) and sulphate (SO42-). Mean, standard deviation, coefficient of variation, Pearson correlation coefficient were used in the summary, analysis and interpretation of the results. The result reveal that the urban land uses and rainwater quality has a significant relationship in Ilorin Metropolis. Agricultural, industrial and institutional land uses have the least significant effect on the quality of rainwater with the significant value of 0.044, 0.035 and 0.014 (P<0.05) respectively. Residential land use has poor rainwater quality with significant value of 0.724 while commercial land use has fairly good quality with 0.585 (P >0.05). The study concludes that the urban land uses has an impact on the rainwater quality. The study recommends that rainwater be purified before drinking and sustainable urbanization policies be developed to prevent atmospheric pollution in Ilorin Metropolis.